Girls Children's Acquisition Rights in Division Inheritance According to Munawir Sjadzali (A Study of the Implementation of the Distribution of Inheritance in the Tradition of the Muslim Batak Tribe and the Minang Tribe in Sidikalang City) - Muhammad Sanif (AT-TAFAHUM: Journal of Law, 2018)
This study describes the thoughts and arguments of Munawir Sjazali through the idea of reactivating Islamic law in inheritance law. Where girls get the same rights as boys equal 1: 1 which is associated with the implementation study of the distribution of inheritance in the traditions of the Muslim Batak tribe and the Minang tribe in the City of Sidikalang. The type of research in writing this thesis is empirical juridical research. With fields and library data collection techniques. The data collection tools are document studies, interviews and observations. Then the data is processed and analyzed descriptively. The results of the research obtained were: First, Munawir Sjadzali gave equal rights between male and female heirs 1: 1. Based on the arguments of the sociological-historical aspects of humanity, that is worldly benefit which will bring humanity to the benefit of ukhrawi. Second, in the tradition of the Muslim Batak tribe and the Minang tribe in the City of Sidikalang the system of inheritance distribution has shifted from customary law to a system of deliberation caused by factors: economic factors, educational factors, factors to maintain the integrity of kinship, factors maintaining the integrity of the fraternity. Third, the implementation or implementation of the distribution of inheritance equals 1: 1 in the tradition of the Muslim Batak tribe and the Minang tribe in Sidikalang city explicitly or markedly not initiated or influenced by Munawir Sjadzali's thoughts, but implicitly or implicitly has the same spirit values as Munawir's thinking Sjadzali.